2006
DOI: 10.1128/mcb.26.2.709-717.2006
|View full text |Cite
|
Sign up to set email alerts
|

The G-Protein-Coupled Receptor GPR103 Regulates Bone Formation

Abstract: GPR103 is a G-protein-coupled receptor with reported expression in brain, heart, kidney, adrenal gland, retina, and testis. It encodes a 455-amino-acid protein homologous to neuropeptide FF2, neuropeptide Y2, and galanin GalR1 receptors. Its natural ligand was recently identified as 26RFa, a novel human RF-amide-related peptide with orexigenic activity. To identify the function of GPR103, we generated GPR103-deficient mice. Homozygous mutant mice were viable and fertile. Their body weight was undistinguishable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 40 publications
5
64
0
Order By: Relevance
“…It is assumed that the loss of tetranectin leads to the softening of the extracellular bone matrix and the intervertebral disk, which then results in spinal deformation. In accordance with that assumption, reduced tetranectin expression was also reported in mice deficient for the G-proteincoupled receptor GPR103, and these mice also developed kyphosis and reduction of trabecular bone (3). Taken together, the observed kyphotic phenotype in NFIX-deficient mice is consistent with reduced expression of tetranectin and suggests that tetranectin is a new downstream target of NFIX.…”
Section: Postnatal Lethality and Gastrointestinal Defects In Nfixsupporting
confidence: 82%
“…It is assumed that the loss of tetranectin leads to the softening of the extracellular bone matrix and the intervertebral disk, which then results in spinal deformation. In accordance with that assumption, reduced tetranectin expression was also reported in mice deficient for the G-proteincoupled receptor GPR103, and these mice also developed kyphosis and reduction of trabecular bone (3). Taken together, the observed kyphotic phenotype in NFIX-deficient mice is consistent with reduced expression of tetranectin and suggests that tetranectin is a new downstream target of NFIX.…”
Section: Postnatal Lethality and Gastrointestinal Defects In Nfixsupporting
confidence: 82%
“…Mice deficient in the receptor for 26RFa/QRFP (Qrfpr) suffer from osteopenia (Baribault et al 2006). This observation indicates that 26RFa/QRFP plays a major role in bone formation, via QRFPR that is expressed in bone (Baribault et al 2006).…”
Section: Comparative Aspects Of Biological Actions Of 26rfa/qrfp In Vmentioning
confidence: 99%
“…26RFa QRFP and GPR103 are expressed in the VMN and the lateral hypothalamus, areas of the brain critically associated with the control of food intake (Chartrel et al 2003, Fukusumi et al 2003, Baribault et al 2006. In fact, in mice, the expression of the peptides is limited almost exclusively to neurons in these two hypothalamic nuclei (Chartrel et al 2003).…”
Section: Kisspeptin Familymentioning
confidence: 99%
“…In addition to pharmacological evidence showing a role for QRFP and 26RFa in food intake, the expression of mRNA for the QRFP/26RFa precursor, measured using real-time reverse transcription (RT)-PCR of dissected tissues, is elevated in the 'hypothalamic' region of fasted mice, as well as in obese ob/ob and db/db mice (Takayasu et al 2006). Importantly, a study looking at bone formation in GPR103-knockout mice reported that body weights are similar between wild-type and knockout littermates, although no data were shown and it was not made clear how the animals were housed or fed (Baribault et al 2006). QRFP has also been reported to have direct effects on aldosterone secretion from rat adrenal gland (Fukusumi et al 2003).…”
Section: Kisspeptin Familymentioning
confidence: 99%